Teaching through turmoil: a collaborative autoethnographic exploration of emergency remote teaching in Malaysian Higher Education / Latisha Asmaak Shafie, Rozilawati Mahadi and Aidura Aiyub - Shafie, Latisha Asmaak; Mahadi, Rozilawati; Aiyub, Aidura (Universiti Teknologi MARA, Perlis, 2023)
The COVID-19 pandemic forced traditional higher education institutions to switch to Emergency Remote Teaching through internet platforms and traditional modes which created significant disruptions. Language educators also were required to conduct online assessments. Using a collaborative autoethnography, we analysed our experiences on Emergency Remote Teaching as three language educators at three Malaysian higher education institutions during the COVID-19 epidemic. We were experts in traditional face-to-face classrooms but novices in online learning environments. The framework for our research was resilience theory. Resilience describes our ability to alter and adapt in the face of adversity. We employed theme analysis to evaluate our self-reflective field notes, which were supplemented with social media posts, from April 2020 to April 2021. Our findings indicate that four themes arose from our research. The findings suggest that four themes emerged from our study; i. strategies used during Emergency Remote Teaching, ii. multiple roles, iii. resiliency, and iv. challenges. The findings give insights into educators' tactics for adapting to the Emergency Remote Teaching environment, their many responsibilities, their resiliency, and the problems they experienced. We feel that our experiences with Emergency Remote Teaching have helped us become better competent language instructors who advocate the synergy of online and offline language study. Our research adds to a better understanding of the experiences that language educators had during Emergency Remote Teaching and the use of these experiences in higher education professional development. These findings are important for policymakers, administrators, and educators as they develop strategies and policies to assist educators in times of crisis.